Answer:
Options 1 and 2 are correct.
Step-by-step explanation:
The graph represents the function
[tex]f(x)=(\frac{1}{2})^{x+1}-2[/tex]
From the given graph it is noticed that the value of f(x) approaches to infinity as x approaches to negative infinity and the value of f(x) approaches to -2 as x approaches to positive infinity.
It can also represented by limits.
As x increases without bound
[tex]lim_{x\rightarrow \infty}f(x)=lim_{x\rightarrow \infty}(\frac{1}{2})^{x+1}-2[/tex]
Apply limit.
[tex]lim_{x\rightarrow \infty}f(x)=(\frac{1}{2})^{\infty+1}-2=0-2=-2[/tex]
As x decreases without bound
[tex]lim_{x\rightarrow -\infty}f(x)=lim_{x\rightarrow -\infty}(\frac{1}{2})^{x+1}-2[/tex]
Apply limit.
[tex]lim_{x\rightarrow -\infty}f(x)=(\frac{1}{2})^{-\infty+1}-2=-2=\infty-2=\infty[/tex]
Therefore as x decreases without bound, f(x) increases without bound and as x increases without bound, f(x) approaches the line y=−2. Options 1 and 2 are correct.